A "teachable moment": using archives to re-examine a new university's identity. Issue 1 (January 2020) - Perez, Heather; Stewart, Courtney
Abstract : Stockton University, located in New Jersey, USA, was named for Richard Stockton, a signer of the United States Declaration of Independence. The University was established in 1969, at the height of the Civil Rights movement in the United States. Yet Richard Stockton enslaved people and signed an oath of loyalty to the British Crown after signing the Declaration as a Revolutionary. How the University came to be named for a slaveholder and a possible turncoat is a complex and conflicting history. In light of events in the United States, such as the removal of Confederate statues and monuments and the renaming of buildings and institutions honouring slaveholders, Stockton University has undergone a critical examination of its own history and identity. Using archives from institutions much older than ours, we studied Richard Stockton's past. From our own archives and founding documents, we analysed how and why the institution bears his name. However, institutional records did not answer all of the questions. Using documentation strategy, the Archivist sought out additional records to add to the collection in order to answer questions about the past and present. Through collecting, researching, teaching and participating in the University project team, the Archivist and a student researcher were able to capitalize on this opportunity raise awareness and used this "teachable moment" to underscore the importance of the University Archives.